Developing a Career Counseling Intervention Program for Foster Youth. Issue 2 (June 2017) - Stevenson, Brian J.
Abstract : Former foster youth often experience difficulty finding and maintaining employment as they emancipate from state care. Research highlights this fact by consistently reporting on the bleak employment outcomes of former foster youth; however, virtually no studies have given practical guidance to practitioners on how to develop interventions. This article addresses this gap in the literature by providing practitioners with a detailed outline of a career counseling group intervention program for foster youth. A brief review of the literature informing this intervention program is also presented.